Marabaixo, ladrão, gengibirra e rádio: traduções de linguagens de textos culturais - Martins, Benedito Rostan Costa (2012)
Men, women and children movements decorating the flagpole, it was Holy Spirit Saturday , boxes, players, women, flowery, swirly skirts, thief etc., drinking ginger beer, purifying the throat for taking the thief . The host offered soup, energy for the revelry. This is marabaixo, the main cultural expression of Amapá, originated from the different relations of expressions, ethnicity, natives and farm-hands from Amazonia. Marabaixo and the regional radio will be the main corpora of our thesis, which title is Marabaixo, thief, ginger beer and radio Translations of languages from cultural texts , A study of the relation between regional media and culture. Our objective is to know marabaixo, interpreting the semiotic systems that mix languages passing through radiophonic language. We are interested in thinking the cultures based on the radio. How is the radio appropriating from cultural texts and how does it influence changes on marabaixo updating. We idealize a communication circuit based on marabaixo movements: detailing possible origins of marabaixo (chapter I); texts from traditional cultures apprehended by the radio, translated and publicized. The circuit is complemented by the reception, where they are evaluated and apprehended. Marabaixo incorporates or not alterations divulged by the radio. Concepts of culture as a Semiotic (Geertz) and Semiosphere system (Lótman and Ferreira) (Chapter II). We see culture as a mediation system, a system formed by marabaixo and radio (Chapter III). We worked the concept of transculturality (Hall), culture as a text (Lótman). Radio has a daily programming with cultural expressions attacking the market audience. The cultural expressions have journalistic values. Mediated and translated signs, on the cultural manifestations, on the radio, by broadcasters, audience, reception etc. On the radio there is technologic mediation. The radio mediation starts being part of the social plot, speeches and social actions (Martín- Barbero). The radiophonic mediation and language translations will be discussed in chapter III. The cultures re-elaborated, reorganize from the communication means